1997
DOI: 10.1002/(sici)1099-1050(199705)6:3<295::aid-hec265>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Output Efficiency of Health Maintenance Organizations in Florida

Abstract: We use data envelopment analysis (DEA) to measure the relative technical efficiencies of 28 HMOs licensed to practice in the State of Florida in the autumn of 1994. Health care output measures used in the analysis are number of commercial, Medicare and Medicaid members enrolled in each plan. Inputs to the model are capital assets, total expenditures on the provision of medical services and administrative expenses. We find differences in HMO efficiency scores and loss ratios (defined as the ratio of expenses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
0
16
0
3
Order By: Relevance
“…Concerning HMOs, a study found that HMOs with Medicaid patients are significantly less efficient than are other HMOs [59]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning HMOs, a study found that HMOs with Medicaid patients are significantly less efficient than are other HMOs [59]. …”
Section: Resultsmentioning
confidence: 99%
“…One study (2%) focussed on the analysis of technical and scale efficiencies for a sample of 28 HMOs in Florida [59]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, to assess the efficiency of the hospital sector DEA has been utilized by the studies like Grosskopf and Valdmanis (1987), Hollingsworth and Parkin (1995), Parkin and Hollingsworth (1997), McKillop, Glass, Kerr, and Mccallion (1999), Hollingsworth, Dawson, and Maniadakis (1999, and so on. Apart from the above, DEA models have been used to assess primary health care services (Salinas-Jiménez & Smith, 1996), to measure the efficiency of health maintenance organizations (Roseman, Siddharthan, & Ahern, 1997), to compare the provision of perinatal services across the United Kingdom (Thanassoulis, Boussofiane, & Dyson, 1995), to compare the education and health efficiency in Organisation for Economic Co-operation and Development (OECD) countries (Afonso & Aubyn, 2005), and to judge the efficiency of government expenditure in Africa (Gupta & Verhoeven, 2001). Spinks and Hollingsworth (2005) assessed health efficiency for OECD countries using DEA-based Malmquist Indexes.…”
Section: Introductionmentioning
confidence: 99%
“…Rosenman et al [34] studied the quarterly and annual reports of 28 HMOs operating in Florida in 1994. They measured outputs as commercial, Medicare, and Medicaid enrollment and inputs as total assets, medical expenditures, and administrative expenditures.…”
Section: Hmo Average Productivitymentioning
confidence: 99%